Coady, Amanda. L to R Mandy Coady and Tommy, Angie and Nicky Boland. - Heritage NL
Amanda Coady provided a picture of (from left to right) Mandy Coady, Tommy Boland, Angie Boland and Nicky Boland. The children stand in a line on the sand. Each of the children in the picture holds a person shaped cookie. There is assorted detritus in the bottom left of the frame.